IN VITRO ANTIOXIDANTS STATUS IN SELECTED INDIAN MEDICINAL PLANTS - VIJAY KUMAR; UMESH KUMAR; MEENAKSHI MISHRA; VEERU PRAKASH (International Journal of Pharma and Bio Sciences, 2012)
Five Indian medicinal plants namely Acorus calamus L, Pelargonium graveolens L, Cymbopogon martini L, Cyambopogon nardus L and Cymbopogon citratus L. were studied for their enzymatic and non enzymatic free radical scavenging properties. Enzymatic ROS scavengers: superoxide dismutase (SOD) and catalase were observed maximum respectively in A. calamus (3.59±0.22 µ mol/min/mg/protein) and P. graveolens (1195.69±0.012 µ mol/min/mg/protein). However, C. citratus which exhibited lowest SOD activity (0.172±0.022), displayed highest activity of ascorbate peroxidase (2.566±0.254 µ mol/min/mg/protein). The ascorbic acid was found to be highest in C. martini (592.09±0.0961 mg/100g) whereas carotenoids were observed maximum in A. calamus (174.8±3.930mg/100g) plant leaves. The total phenolic content (Folin-Ciocalteu assay) was shown to be highest in P. graveolens leaves (22.27±0.284mg GAE ml-1) followed by C. citrates, C. martini, C. nardus and A. calamus. The findings indicated promising free radical scavenging activity of the above plants and needs further exploration for their effective use in medicines.